2003
DOI: 10.1007/s00417-003-0728-3
|View full text |Cite
|
Sign up to set email alerts
|

Physical and cytological characters of carbon, titanium surface modified intraocular lens in rabbit eyes

Abstract: The optical characteristics of C, T-IOL) were stable in rabbit eyes after 1 year of implantation. The C, T-IOLs became hydrophobic compared with PMMA-IOLs. They also induced foreign body reactions similar to those seen with PMMA-IOLs in rabbit eyes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…As several studies [20][21][22] show, surface modification is a promising way to alter the character of the surface of an IOL without changing the bulk. In the present study, contact angle results showed that a new IOL with a hydrophilic anterior surface and a hydrophobic posterior surface was successfully prepared through plasma treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As several studies [20][21][22] show, surface modification is a promising way to alter the character of the surface of an IOL without changing the bulk. In the present study, contact angle results showed that a new IOL with a hydrophilic anterior surface and a hydrophobic posterior surface was successfully prepared through plasma treatment.…”
Section: Discussionmentioning
confidence: 99%
“…20 The more hydrophilic the IOL surface, the less adhesive and proliferative the cells. 26,27 Hydrophilic heparin-surface-modified IOLs are one successful example of surface modification in which hydrophilic moieties are used to reduce protein and cell adhesion; these IOLs yield a significantly lower inflammatory response after cataract extraction than unmodified poly(methyl methacrylate) IOLs.…”
Section: Discussionmentioning
confidence: 99%
“…Carbon and titanium IOLs belong to the hydrophobic IOL category. Their contact angles were 80 and 84.5, respectively [26].…”
Section: Discussionmentioning
confidence: 99%
“…They were produced from the same model of PMMA IOL as mentioned above. These IOLs were produced by carrier energy ion beam (carbon or titanium) combined with low temperature and low-pressure plasma as described elsewhere [26]. DOI 10.1007/s00417-004-0970-3 Animals Sixty Japanese albino rabbits of both sexes with an initial body weight range of 1.5-2.0 kg (4 months old) were obtained and raised in a control environment in Tianjin Medical University Animal Department.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation